KINETICS OF TRAINED HORSES WITH PESSOA'S REIN - da Silva, D. A.; Oliveira, K.; Pereira, A. M.; Duarte, A. C. A. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The objective of this study was to evaluate the use of the Pessoa rein, in athlete horses, through the kinetic analysis of the walk and the trot gaits. Twelve horses, aged five years and weighing an average of 400 kg, were used. Two treatments were used, in the first group, the horses were trained the guide without the use of the Pessoa rein and in the second treatment the training was done using the Pessoa rein. The experimental design was completely randomized, with six replicates per treatment. The variables monitored were: dorso-ventral (DVF), propulsion (PF), mid-lateral (MLF) and total (TF) forces in the walk and trot gaits. There was no significant improvement in the kinetic parameters evaluated in the walk gait for horses trained without the rein Person. For horses trained with rein Person, there were significant increases in DVF and PF forces in walk gait, obtaining final mean values ​​of 0.84 and 1.49 W / kg, respectively. There was an improvement in the development of the three components of forces, such as DVP, PF and TF (P <0.05), at trot gait, only for horses trained with the Pessoa rein. It was concluded that the training with rein Pessoa modified the kinetics of displacement of the walk and trot gaits in horses. And that the trot of horses, submitted to the rein with Person training, presented greater propulsion, as well as improvements of the dorso-ventral and total forces.